Mekanisme Pengangkatan Anak Kontemporer: Analisis Horizontal dan Vertikal di Negara Muslim Dunia - Bariki, Yusril (Pamulang Law Review, 2024)
One of the family law reforms that is most widely promoted in modern Muslim countries is adoption. Until now, adoption or what is commonly known as adoption is a form of legal action that has important implications for the legal status of several parties involved. This research uses a comparative descriptive approach by analyzing the history and legal basis for adoption, as well as comparing the implementation of polygamy regulations in Muslim countries such as Indonesia, Malaysia, Pakistan, Turkey, Tunisia, Egypt, Morocco, Syria and Jordan. All countries allow adoption, but in formalistic regulations there are 2 mechanisms for adopting children, namely through the judiciary and the kafalah system.